Towards a unified theory of domestic hydrogen acceptance: an integrative, comparative review - Gordon, Joel A.; Balta-Ozkan, Nazmiye; Nabavi, Seyed Ali (Elsevier, 2024)
Hydrogen energy technologies are envisioned to play a critical supporting role in global decarbonisation. While low-carbon hydrogen is primarily targeted for reducing industrial emissions, alongside decarbonising parts of the transport sector, environmental benefits could also be achieved in the residential context. Presently, gas-dependent countries such as Japan and the United Kingdom are assessing the feasibility of deploying hydrogen home appliances, as part of their national energy strategies. However, prospects for the transition will hinge on consumer acceptance, alongside an array of other socio-technical factors. To support potential ambitions for large-scale and sustained technology diffusion, this study advances a Unified Theory of Domestic Hydrogen Acceptance. Through an integrative, comparative literature review targeting hydrogen and domestic energy studies, the paper proposes a novel Domestic Hydrogen Acceptance Model (DHAM), which accounts for the cognitive and emotional dimensions of human perceptions. Through this dual interplay, the proposed framework can increase the predictive power of hydrogen acceptance models.
Keywords: Cognitive processes; Domestic energy acceptance; Emotional dimensions; Hydrogen energy acceptance; Social trust; Technological perceptions